New dating approach based on the petrographical, mineralogical and chemical characterization of ancient lime mortar: case study of the archaeological site of Hippo, Annaba city, Algeria. - gheris abderrahim (Heritage Science, 2023)
This work presents the results of a multidisciplinary study on the characterization of the composition of certain joint mortars from the ancient city of Hippo (Algeria), one of the most important North African cities in antiquity. Twenty mortar samples were analysed by X-Ray Fluorescence (XRF), powder X-ray diffraction (XRPD), optical microscopy (OM), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDS) and thermogravimetric analysis (TGA). Their main physical properties, like solid and dry density and porosity, have been measured by geotechnical procedures. The typological observation by OM showed the existence of four types of sand used as aggregates that ranged from fine to coarse and were mixed with a white to russet natural lime binder. These mortars consisted mainly of mixtures of calcite and rock fragments, and sometimes pieces of red tile. It was recognized that the origins of the natural granules were sands produced by marine erosion of the Edough Mountains. The analysis by XRPD and TGA indicates that the mortars consisted of a mixture of lime/aggregates of low to medium hydraulicity. The analysis of the main chemical components by XRF allowed for the confirmation of the dating of certain monuments and suggested a new dating for other monuments.
Keywords: Petro physical analysis; Lime mortar; Aggregate; Roman ruin; Hippo Regius